High Sensitivity C-Reaktive Protein (Hs-CRP) dan LED sebagai Penanda Inflamasi pada Penderita Tuberculosis (TBC) - Ni Nyoman Ariwidiani (Jurnal Skala Kesehatan, 2026)
Mycobacterium tuberculosis infection increases IL-6 production, thereby inducing liver cells to synthesise active phase proteins, such as CRP. Increased levels of Hs-CRP and ESR are often associated with inflammation and acute infection. This study aims to determine the relationship between Hs-CRP and ESR levels as markers of inflammation in TB patients. Data collection was conducted using an analytical observational method with a cross-sectional design. Samples were obtained via simple random sampling, with a sample of 20 tuberculosis patients. Measurement of Hs-CRP levels was carried out using ELISA, while measurement of ESR levels was carried out using Roller 20. Data analysis was carried out using a statistical correlation test to determine the relationship between the two test variables. Based on the measurement data for Hs-CRP and ESR levels, the average Hs-CRP level was 3.32 mg/L, and the average ESR level was 54.55 mm/h in tuberculosis patients. Statistical correlation test shows the relationship between Hs-CRP levels and ESR in tuberculosis patients (p=0.042 with moderate correlation and positive correlation direction (t=0.458). Overall, there is a moderate, positive correlation between Hs-CRP levels and LED, a marker of inflammation, in tuberculosis patients.